Application of UAV Remote Sensing in Monitoring Water Use Efficiency and Biomass of Cotton Plants Adjacent to Shelterbelt - Ma, Bin; Wang, Qijie; Xue, Bing; Hou, Zhenan; Jiang, Yan; Cai, Wenyue (Frontiers in Plant Science, 2022)
Tree shelterbelts are crucial for maintaining the ecological environment of oasis, but they may also compete for soil water with adjacent crops, affecting crop yields. To evaluate the impacts of shelterbelt on water use efficiency (WUE) and normalized water productivity (WP) of adjacent cotton plants, the biomass (B) and WUE of cotton with different distances from the shelterbelt (0.1H, 0.5H, 1H, 2H, and 3H; H (average tree height=15 m)) were estimated based on UAV remote sensing data combined with the FAO crop water response model AquaCrop. Besides, the accuracy and universality of the estimation method were also evaluated. The results showed that the method based on UAV remote sensing data and AquaCrop can accurately estimate the impact range and intensity of shelterbelt on WUE, water consumption, and biomass of adjacent cotton plants. Fierce water competition between shelterbelt and cotton was detected within 0.1H ~ 1H, and the competitiveness of shelterbelt was weaker in the plots >1H than in the 0.1H ~ 1H. The B, actual evapotranspiration (Tc), and WUE of cotton at 0.1H decreased by 59.3%, 48.8%, and 23.6%, respectively compared with those at 3H, but the cotton plants at 2H and 3H were completely unaffected by the shelterbelt. Besides, the B estimated based on WP (RMSE = 108 g/m2, d = 0.89) was more accurate than that estimated based on WUE (RMSE = 118 g/m2, d = 0.85). This study clarifies the inter-species competition for soil water between crops and shelterbelt under drip irrigation in oases in China.